Are Audit-related Ethical Decisions Dependent upon Mood? - Curtis, Mary B. (Journal of business ethics, 2006)
This study explores the impact of mood on individuals’ ethical decision-making processes through the Graham [Graham, J. W.: 1986, Research in Organizational Behavior 8, 1–52] model of Principled Organizational Dissent. In particular, the research addresses how an individual’s mood influences his or her willingness to report the unethical actions of a colleague. Participants’ experienced an affectively charged, unrelated event and were then asked to make a decision regarding whistle-blowing intentions in a public accounting context. As expected, negative mood was associated with lower intentions to report the unethical actions of others to a superior within the organization. The Graham model, which proposes that reporting intentions are impacted by the three determinants of seriousness, personal responsibility and cost, was employed to more clearly understand the nature of the affect–reporting intention relationship. The role of affect was explained by demonstrating that two determinants mediate the relationship between mood and whistle-blowing intentions. Specifically, as seriousness and responsibility have a positive impact on reporting intentions, the reduction of these perceptions by negative mood reduces the intent to report. The negative impact of personal cost on reporting intentions was significant, although not as a mediator of mood.